Physical parameters of shock-accelerated electron region estimated from observations of solar metric band-split type II burst - Silva , R. D. C.; Fernandes , F. C. R.; Selhorst , C. L. (Physicae Proceedings, 2020)
This study presents the analysis of a solar split-band type II radio burst observed on November 3, 2010 (? 10:17:14 UT) by CALLISTO-BR (Compound Astronomical Low frequency Low Cost Instrument for Spectroscopy and Transportable Observatory) spectrometer operating in the frequency range of 45-870 MHz. Among the physical parameters determined for the shock propagation region are: source speed of the order of 1033 km s^?1 ; electron number density of ? 8.6 × 10^8 cm^?3 ; Alfvén speed of the order of 2007 km s^?1 ; Mach number of ? 1.09 ? 1.33; magnetic field strength of ? 7 ? 177 G and temperature of the order of 6.0 × 10^6 K. The outcomes, compared to those reported in the literature, are consistent, taking into account the fact we are dealing with an atypical type II radio burst, namely, one with high starting frequency, what accounts for the very high Alfvén speeds estimated for the initial altitudes of propagation of the shock through the solar corona.